Pengaruh Variabel Makroekonomi Terhadap Indeks Harga Saham Gabungan (Studi pada Indeks Harga Saham Gabungan di Bursa Efek Indonesia Periode 2014-2018) - Mamahit, Rina R.; Tumbel, Tinneke M.; Mangindaan, Joanne V. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This research aims to determine whether the macroeconomic variables i.e., the exchange rate, inflation and BI rate simultaneously and partially influence Indonesia Composite Index at The Indonesia Stock Exchange (IDX). The approach in this study is a quantitative method, using multiple linear regression analysis. The data used are time series data from January 2014 until December 2018. The result indicates that exchange rates, inflation and BI together have a significant impact to Indonesia Composite Index. Individually, only the BI rate variable has a significant effect and has a negative effect to Indonesia Composite Index. The exchange rate and inflation had no significant effect to Indonesia Composite Index.